2001
DOI: 10.5089/9781451857092.001
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Exchange Rate Regimes in Post-Crisis East Asia

Abstract: The views expressed in this Working Paper are those of the author(s) and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author(s) and are published to elicit conunents and to further debate. WPI01/152This paper examines the behavior of the exchange rates of selected emerging market East Asian economies in the aftermath of the Asian crisis. The results suggest that movements in the Asia-5 currencies (Indonesia, Korea, Malaysia, Philippines, and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 3 publications
0
27
0
Order By: Relevance
“…Using Frankel and Wei's (1994) methodology, they analyze the relative importance of USD and JPY in determination of Asian currencies exchange rates. For instance, Baig (2001), for the sample period of 1995-2000, evaluates the relative importance of the USD, German Mark, and JPY in emerging Asian currencies' exchange rates and reports a relatively more important and stable role of JPY. McKinnon and Schnable (2004) report, however, that the USD is still dominant currency in exchange rate determination in this area.…”
Section: Previous Studiesmentioning
confidence: 99%
“…Using Frankel and Wei's (1994) methodology, they analyze the relative importance of USD and JPY in determination of Asian currencies exchange rates. For instance, Baig (2001), for the sample period of 1995-2000, evaluates the relative importance of the USD, German Mark, and JPY in emerging Asian currencies' exchange rates and reports a relatively more important and stable role of JPY. McKinnon and Schnable (2004) report, however, that the USD is still dominant currency in exchange rate determination in this area.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The findings of recent relevant studies are summarized below. Baig (2001) compared the relative importance of the USD, the German mark, and the JPY in East Asian-countries' exchange rates over the period 1995-2000 and found that the relative importance of the JPY remained stable. On the other hand, McKinnon and Schnabl (2004) reported that while there is evidence of increased co-movement of the two bilateral rates, the USD was still the dominant currency in determining exchange rates in this area.…”
Section: Previous Studiesmentioning
confidence: 96%
“…The preference for extreme regimes was given legitimacy against the worst memories of steep and abrupt devaluations of most regional currencies during the crisis. By using a flexibility index, Baig [2] observes that exchange rates in the region have become more flexible now than the pre-crisis years and weight to the USD has diminished in respective country currency baskets.…”
Section: Justification For Choice Of Exchange Rate Regime In Economicmentioning
confidence: 99%